Calculating Essential Biodiversity Variables for species population abundance in the Baltic Sea - Obst, Matthias (University of Gothenburg, 2018)
This data set contains the documentation of the BALTIC data set analysis as a part of the manuscript 'Building essential biodiversity variables (EBVs) of species distribution and abundance at a global scale' by

Kissling, W. D., et al. (2018), Building essential biodiversity variables (EBVs) of species distribution and abundance at a global scale. Biol Rev, 93: 600-625. doi:10.1111/brv.12359

The data set contains input and output files, geographic locations, and R scripts.

This data set contains the documentation of the BALTIC data set analysis as a part of the manuscript 'Building essential biodiversity variables (EBVs) of species distribution and abundance at a global scale' by

Kissling, W. D., et al. (2018), Building essential biodiversity variables (EBVs) of species distribution and abundance at a global scale. Biol Rev, 93: 600-625. doi:10.1111/brv.12359

The data set contains input and output files, geographic locations, and R scripts.

Innehåller data för BALTIS-analysen som genomfördes för "Building essential biodiversity variables (EBVs) of species distribution and abundance on a global scale" som ingår i: Kissling, W. D., et al. (2018), Bygga väsentliga biodiversitetsvariabler (EBV) av artdistribution och överflöd på global nivå. Biol Rev, 93: 600-625. doi: 10,1111 / brv.12359

Datasetet består av inmatnings- och utdatafiler, geografiska platser och R-skript.

This data set contains the documentation of the BALTIC data set analysis as a part of the manuscript 'Building essential biodiversity variables (EBVs) of species distribution and abundance at a global scale' by

Kissling, W. D., et al. (2018), Building essential biodiversity variables (EBVs) of species distribution and abundance at a global scale. Biol Rev, 93: 600-625. doi:10.1111/brv.12359

The data set contains input and output files, geographic locations, and R scripts.
Calculating Essential Biodiversity Variables for species population abundance in the Baltic Sea
Keywords: MARINE ENVIRONMENT MONITORING; BIOSPHERE; AQUATIC ECOSYSTEMS; PLANKTON; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biota; Biologi och ekologi